Oligodendrocyte Differentiation from Human iPSCs: Strategies Based on Signaling Pathways, Transcription Factors, and Novel Modulators for Research and Therapy - Maria Maylyn Evangelina Wong; Michelle Angelica Subrata (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Oligodendrocytes (OLs) are vital for central nervous system (CNS) function, producing myelin sheaths and maintaining axonal integrity. However, their limited accessibility in human disease-relevant contexts has historically hindered progress in research. The advent of induced pluripotent stem cell (iPSC)-derived OLs has transformed the study of myelin-related diseases and regenerative therapies. Objective: This review aims to provide a comparative overview of strategies for generating OLs from human iPSCs, emphasizing their mechanisms, efficiency, scalability, and translational applications. Methods: We analyzed three major differentiation approaches described in recent literature. Signaling-based protocols replicate developmental processes by modulating TGF-β, SHH, and Wnt pathways. Transcription factor-driven methods accelerate lineage specification by directly inducing OL fate. Modulator-enhanced strategies incorporate epigenetic, metabolic, or environmental cues to improve efficiency and adaptability. Results: Each approach offers distinct strengths and limitations. Signaling-based methods closely mimic in vivo development but require long culture times. Transcription factor-driven strategies enable rapid OL generation, although sometimes at the expense of physiological relevance. Modulator-enhanced protocols represent an emerging avenue, offering flexibility and potential for higher efficiency. Collectively, these strategies expand opportunities for disease modeling, therapeutic screening, and cell replacement therapies. Conclusion: Advances across signaling, transcriptional, and modulatory domains have significantly advanced iPSC-based OL generation. Integration of these approaches may enable more efficient, scalable, and physiologically relevant OL production. Such progress holds significant potential to accelerate the development of myelin targeted therapeutics and enhance translational research in demyelinating diseases.